2014
DOI: 10.1155/2014/240473
|View full text |Cite
|
Sign up to set email alerts
|

Chylous Ascites: Evaluation and Management

Abstract: Chylous ascites refers to the accumulation of lipid-rich lymph in the peritoneal cavity due to disruption of the lymphatic system secondary to traumatic injury or obstruction. Worldwide, abdominal malignancy, cirrhosis, and tuberculosis are the commonest causes of CA in adults, the latter being most prevalent in developing countries, whereas congenital abnormalities of the lymphatic system and trauma are commonest in children. The presence of a milky, creamy appearing ascitic fluid with triglyceride content ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
196
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(205 citation statements)
references
References 103 publications
2
196
0
7
Order By: Relevance
“…Loss of chyle into peritoneal cavity can lead to serious consequences because of the loss of essential proteins, lipids, immunoglobulins, vitamins, electrolytes, and water. If drain is not placed then repeated therapeutic paracentesis provides relief from symptoms but the nutritional deficiency will continue to persist or deteriorate unless definitive therapeutic measures are instituted to stop leakage of chyle into the peritoneal space (6). In case of persistent chyle leakage even after dietary interventions, c ase reports have suggested that both somatostatin and octreotide either alone or in combination with TPN are effective in the management (7).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Loss of chyle into peritoneal cavity can lead to serious consequences because of the loss of essential proteins, lipids, immunoglobulins, vitamins, electrolytes, and water. If drain is not placed then repeated therapeutic paracentesis provides relief from symptoms but the nutritional deficiency will continue to persist or deteriorate unless definitive therapeutic measures are instituted to stop leakage of chyle into the peritoneal space (6). In case of persistent chyle leakage even after dietary interventions, c ase reports have suggested that both somatostatin and octreotide either alone or in combination with TPN are effective in the management (7).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Despite the fact that ascites are a common manifestation of hepatic cirrhosis, CA presents in only 0.5%–1% of patients with cirrhosis 2. A recent systematic review showed that cirrhosis was responsible for 11% of atraumatic CA 1…”
Section: Differential Diagnosis and Further Investigationsmentioning
confidence: 99%
“…Constrictive pericarditis and severe right heart failure have been reported to cause CA 2. They cause impaired lymph drainage with consequent thoracic duct dilatation and hypertension, leading to an increase in hepatic venous pressure, thereby increasing lymph production 4…”
Section: Differential Diagnosis and Further Investigationsmentioning
confidence: 99%
“…Due to their lower molecular weight, medium-and short-chain triglycerides (such as fats derived from butter) can be absorbed by mucosal cells of the gut and transported as free fatty acids and glycerol to the liver through the portal circulation ( Figure 1). 8 Medium-and short-chain triglycerides are more hydrosoluble than long-chain triglycerides. This property permits their direct diffusion from the epithelial cells to the blood in the capillaries of the intestinal villi, so the intestinal lymphatic flow is bypassed.…”
Section: Managementmentioning
confidence: 99%